Crisis, what crisis? Patterns of adaptation in European labor markets - Werner Eichhorst; Michael Feil; Paul Marx (Institute for the Study of Labor (IZA), 2010)
The current crisis, while of a global nature, has affected national labor markets to a varying extent. While some countries have experienced a steep increase in unemployment, employment in other developed economies has not fallen in parallel with a significant decline in GDP. Our analysis shows that labor market institutions frequently used to study employment performance can explain the development of unemployment in the situation of crisis in some clusters of countries much better than in others. One major factor to be incorporated in capturing national variations is the role of internal flexibility, in particular working time adjustment. This calls for a broader concept of labor market flexibility which takes into account different channels of adjustment.
Keywords: J23; J21; J58; 330; Labor market institutions; internal flexibility; employment protection; economic crisis; Wirtschaftskrise; Beschäftigungseffekt; Arbeitslosigkeit; Arbeitsmarktflexibilisierung; Arbeitnehmerschutz; Arbeitszeitflexibilisierung; Vergleich; Europa